AB0633 REAL WORLD EXPERIENCE OF THE IMPACT OF SECUKINUMAB ON DISEASE ACTIVITY AND FATIGUE IN PATIENTS WITH ANKYLOSING SPONDYLITIS. (2nd June 2020) - Batool, S.; Bawa, S.
Abstract : Background: Fatigue is one of the most commonly reported symptom of ankylosing spondylitis (AS). It impacts functional ability, quality of life, and ability to maintain employment 1 . Secukinumab, a fully human monoclonal IgG1 antibody that neutralizes IL-17A, has shown significant and sustained improvement in the signs and symptoms of active AS in the MEASURE 2 study 2 . It has also shown to improve fatigue scores. Despite this, the published literature on real life experience is scarce. We report our experience of Secukinumab use at Gartnavel General Hospital, Glasgow, UK. Objectives: We performed a retrospective review to assess the response of our AS patients to Secukinumab. We also reviewed the impact of treatment on fatigue. Methods: AS patients commenced on Secukinumab 150mg subcutaneously from mid-2016 to September 2019 were identified using the clinical records on our database. Response using Bath AS disease activity index (BASDAI) and Bath AS function index (BASFI) were recorded. Impact on fatigue and pain was measured using single-item fatigue and pain visual analogue scale (VAS) within the BASDAI questionnaire. Results: 30 AS patients, 11 anti-TNF naïve and 19 anti-TNF inadequate responders (IR), on Secukinumab were identified. Retention rate was 76.66% (23/30). Sustained improvement was observed across all outcome measures over 3.5 years. Fatigue and pain improvement were somewhat lower than expected but did show slow improvement. Responses were greater in anti-TNF naïve patients. There was no significant difference in response between smokers (33.34%, 10/30) and non-smokers (36.67%, 11/30). There were 4 patients with inflammatory bowel disease, none of whom flared. No new safety signals were identified. Conclusion: In our real-life cohort of AS patients, significant improvement was seen over 3.5 years in both BASDAI and BASFI. Fatigue was significantly improved in anti-TNF naïve group, but results were disappointing in anti-TNF IR group. This may be explained by the fact that there are older patients with established disease and background degenerative changes in anti-TNF IR group. Although fatigue data had slightly discordant results compared with the MEASURE 2 study 2, considering the use of single item VAS rather than multidimensional measures such as FACEIT fatigue scale, clear improvement has been observed. References: [1]E. E. Schneeberger, M. F. Marengo, F. Dal Pra, J. A. Maldonado Cocco, and G. Citera, "Fatigue assessment and its impact in the quality of life of patients with ankylosing spondylitis, " Clin Rheumatol, vol. 34, no. 3, pp. 497–501, 2015. [2]H. Marzo-Ortega, J. Sieper, A. Kivitz, R. Blanco, M. Cohen, R. Martin, A. Readie, H. B. Richards, and B. Porter, (2017) 'Secukinumab and Sustained Improvement in Signs and Symptoms of Patients With Active Ankylosing Spondylitis Through Two Years: Results From a Phase III Study', Arthritis Care & Research, Vol. 69, No. 7, July 2017, (DOI 10.1002/acr.23233), pp. 1020–1029. Acknowledgments: S. Kerr, K. Anderson and Rheumatology department, Gartnavel General Hospital, Glasgow, UK Disclosure of Interests: None declared